Pemanfaatan Media Sosial untuk Promosi Usaha Kuliner pada Warung Bakso Mas Arif di Kota Padang - Fitrah Sari; Silvia Iskandar; Deni Amelia; Hesti Maria Putri (PT. TAKAZA INNOVATIX LABS, 2023)
Community Service is a form of the Tridarma of Higher Education. This Community Service is purpose to carry out socialization and educational activities in Culinary Business SMEs at Warung Bakso Mas Arif in Padang City. The general objective of this community service activity is to provide additional knowledge and understanding of the efforts that can be made by business owner to increase sales through increased promotion or marketing by utilizing social media. In this case business owners can make efforts to increase sales through the use of social media which is one of the business solutions in increasing their business marketing. By utilizing social media platform wisely, these SMEs can expand their market reach, build relationships with costumers and promote their products or services but in an easier and free way.